Overview Of Student'S Motivation In Taking Music Extracurricular At Public Senior High School I Padang - Rindiani Ningsih; Solfema Solfema (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the high non-academic achievement of SMA Negeri 1 Padang students in the field of music. This is supported by the complete facilities owned by the music extracurricular, good guidance from music extracurricular teachers, good guidance from seniors, and a strong desire from within the students themselves. The purpose of this study was to see a description of students' persistence in participating in extracurricular activities in music, to see a description of students' attitudes when facing difficulties in learning musical instruments, and to see students' enthusiasm in practicing during the music art extracurricular training process. The type of research used is descriptive quantitative. The population in this study were all students who were members of the extracurricular music arts at SMA Negeri 1 Padang, while the sample was taken partly from the total population. The data collection technique used a questionnaire distributed to the sample. The data is then processed using the percentage formula. The results showed that (1) students were always diligent in participating in extracurricular activities in music; (2) students have a good attitude in overcoming difficulties during extracurricular activities in music; (3) students are always enthusiastic to carry out music art extracurricular exercises. Based on the results of the study, it is recommended that students continue to increase their motivation so that they can maintain and improve their non-academic achievements. Meanwhile, for the builder teacher to continue to direct and guide the students of extracurricular members of the art of music in practicing so that students' self-motivation is not lost, thereby reducing students' interest in practicing music.Keywords: motivation, perseverance, attitude, and spirit.